2018
DOI: 10.1111/1462-2920.14485
|View full text |Cite
|
Sign up to set email alerts
|

Community structural differences shape microbial responses to high molecular weight organic matter

Abstract: Summary The extent to which differences in microbial community structure result in variations in organic matter (OM) degradation is not well understood. Here, we tested the hypothesis that distinct marine microbial communities from North Atlantic surface and bottom waters would exhibit varying compositional succession and functional shifts in response to the same pool of complex high molecular weight (HMW‐OM). We also hypothesized that microbial communities would produce a broader spectrum of enzymes upon expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 68 publications
9
47
0
Order By: Relevance
“…This implies that differences in microbial community composition will result in variations in carbon remineralization rates independent of environmental conditions. For example, the addition of high‐molecular weight DOM to seawater mesocosms prepared from distinct water masses led to increased extracellular hydrolytic activity as well as growth of 'rare' OTUs (Balmonte et al ., ). Moreover, the spectrum of active enzymes detected in these mesocosms varied considerably, which suggested that the substrates that would have been consumed also differed among communities.…”
Section: Discussionmentioning
confidence: 97%
“…This implies that differences in microbial community composition will result in variations in carbon remineralization rates independent of environmental conditions. For example, the addition of high‐molecular weight DOM to seawater mesocosms prepared from distinct water masses led to increased extracellular hydrolytic activity as well as growth of 'rare' OTUs (Balmonte et al ., ). Moreover, the spectrum of active enzymes detected in these mesocosms varied considerably, which suggested that the substrates that would have been consumed also differed among communities.…”
Section: Discussionmentioning
confidence: 97%
“…Differential longterm responses of the microbial communities in Stn. 4 surface and bottom waters to amendment with HMW DOM (Balmonte et al, 2019) indicate that these distinct water masses also have distinct microbial community structure and function, with differing potential impacts on the carbon cycle. These patterns in functional biogeography mirror biogeographical patterns in microbial community composition (Fuhrman et al, 2008;Zinger et al, 2011;Ladau et al, 2013;Nelson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Glucosidase activities were measured using the following methylumbelliferyl (MUF)-labelled compounds: α-glucopyranoside (α-glu) and β-glucopyranoside (β-glu). Whereas Leu, α-glu, and β-glu have been used in a wide range of environmental settings, substrate proxies measuring chymotrypsin and trypsin activities have been used only in a limited number of systems (e.g., Arnosti, 2015;Balmonte et al 2019;Balmonte et al 2020;Bong et al 2013;Obayashi and Suzuki, 2005;Steen and Arnosti, 2013).…”
Section: Methodsmentioning
confidence: 99%